(untitled) (diségno, 2019)
The representation of the image characterizing an urban environment has always been a complex challenge for those involved in documentation and Drawing, because it contains a multiplicity of aspects that it is not always possible to measure and graphically return. The immaterial aspects are the ones that most characterize the image of a city, together with all those characteristics that derive from the evolutionary history of the city itself, which are decisive for its current configuration, but which it is not always easy to grasp. A set of relationships, colours, materials and lights that go beyond the quantitative aspects expressed by forms and dimensions, which sometimes even the most advanced digital representation seems not to fully render. In fact, the system of representation used for the communication of the physical consistency of an urban environment must try to explain all the elements that contribute to the definition of the image, elaborating a representation that not only manifests geometric/dimensional instances, but it also shows the formal/qualitative ones, the one that are useful for the understanding of the elements that characterize in a unique way the image of each specific urban reality. This text collects a series of reflections on the various meanings of the representation of the urban environment, briefly referring to two case studies of different nature, which, as examples, can help to frame the complexity of the issues involved.